The Role of Teachers in Building National Character Values through Traditional Games for Elementary School Students - Lukman Praja, Azis; nurfaidah, siti sholiha; Rahmiati, Devi (Universitas Pendidikan Ganesha, 2018)
Rapid technological and information developments have impacted changes in various lines of life. The big impact that arises from the changes that occur is the decline in the values of the nation's character. The problem solving effort is by providing guidance in improving the ability of educators in shaping the values of the national character of elementary school students. The targets in this activity are the Teacher Working Group (KKG) in SD PBI and KKG in SDN 208 Luginasari. The method used in the form of organizing seminars and workshops on the role of teachers in building national character values to elementary school students. The activity was carried out quite well. Teachers are given debriefing and skills to carry out learning activities that contain character education through traditional game intermediaries. Suggestions for the achievement of the objectives of this activity is that assistance is still needed for the teacher so that the teachers can consistently transform their knowledge and skills in the path that we all expect.